Effect of a School-based Intervention Based on Social Cognitive Theory on Fruit and Vegetable Consumption in Middle School Students in Tehran - Farinaz Abbasian; Nasrin Omidvar; Dolly Bondarianzadeh; Bahram Rashidkhani; Elham Shakibazadeh; Baran Hashemi (Tehran University of Medical Sciences, 2012)
Background & Aim: Diet rich in fruits and vegetables is shown to be an important factor in prevention of chronic diseases. Adolescence is a critical period in adopting eating behaviors. Schools are important social environments in adolescentschr('39') lives and are important settings for interventions that aim to improve eating behaviors, including fruit and vegetable intake. This study aimed to assess effectiveness of a school-based intervention based on social cognitive theory on fruit and vegetable (F&V) intake of female adolescents in Tehran. Methods & Materials: This experimental school based field trial was conducted on 296 female students aged 10-13 years old (157 in the intervention and 139 in the control groups). The intervention included classroom nutrition education on F&V and increasing availability of F&V through school buffet. Psychosocial characteristics of the students were assessed using a questionnaire and F&V intake were measured using 24-hr recall method, at baseline and after three months intervention. Descriptive and inferential statistics were used for data analysis. Results: After the intervention, vegetable and fruit intake were 0.6 and 0.63 servings higher in the intervention group compared to the controls. Knowledge and self-efficacy scores were significantly higher in the intervention group compared to the control group. Home availability and observational learning scores were significantly decreased in the intervention group. Conclusion: Through the intervention process, many valuable experiences were gained to be used in future interventions.